Participación y ciudadanía en tiempos de globalización - Cruz, Manuel Braga da (2003)
Social and political participation is a value and an essential dimension of modern democracies. But the decrease of this participation in the most developed contemporary societies affects their civic culture and the foundations of democratic legitimacy. Citizenship, wich is the basis of modern concept of nation, evolved from the early concept of civil liberty, at the beginning of the 19th century, and from the notion of political equality, at the end of the same century, to the later idea of social solidariety, already in the 20th century. This conception of citizenship has been transleted, from the juridical point of view, into the notion of nationality. With the advent of post-industrial and post-materialistic societies, and the spreading of globalization, social and cultural identities are reformulated, citizenship becames transnational, and participation becames not only national, but also infra and supra national.